Pengaruh Motivasi dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru di SD Negeri 04 Oku - Fitri Rahmadanti; Fifian Permata Sari; Rini Efrianti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the influence of motivation and leadership of the principal on the performance of teachers of SDN 04 OKU. The population of this study consisted of 32 respondents. Quantitative Method Tools using multiple linear regression analysis as an analysis tool. The results of the analysis show that the t value for each variable Motivation (X1) is 8.813 and Principal Leadership (X2) is 3.003. These values are greater than the critical t value of 2.045, indicating that all variables have a significant influence on the performance of teachers of SDN 04 OKU. The calculated F value of 215.999 is greater than the critical F value of 3.33, indicating that motivation and leadership of the principal together have a significant influence on the performance of teachers of SDN 04 OKU. The coefficient of determination (R-squared) is 0.937, indicating that 93.7% of teacher performance (Y) can be explained by the variables of motivation (X1) and principal leadership (X2), while the remaining 6.3% is influenced by other variables not examined in this study.